Skull Bone Regeneration Using Chitosan-Siloxane Porous Hybrids-Long-Term Implantation - Yuki Shirosaki; Motomasa Furuse; Takuji Asano; Yoshihiko Kinoshita; Toshihiko Kuroiwa (MDPI AG, 2018)
Burr holes in craniotomy are not self-repairing bone defects. To regenerate new bone at the sites of these defects, a good scaffold is required. Biodegradable hybrids including silica or siloxane networks have been investigated as bone tissue scaffolds. This study examined skull bone regeneration using chitosan-siloxane hybrids after long-term implantation (two and three years). After implantation of the hybrids, the surrounding cells migrated and formed fibrous tissues and blood vessels. Then, bone formation occurred from the surrounding blood vessels. Addition of calcium ions and coating with hydroxyapatite improved bone regeneration. Finally, the regenerated tissue area became smaller than the initial hole, and some areas changed to completed bone tissues.